Organization Performance and Leadership Style: Issues in Education Service. (15th June 2016) - Wahab, Samsudin; Rahmat, Adlan; Yusof, Mohd Sukor; Mohamed, Badrisang
Abstract: Leadership has been recognized as a vital focus in the field of organizational behaviour in which it is one of the dynamic effects during individual and organizational interactions. Leadership undoubtedly has the major role in the outcome of any project in which all identified leadership styles have variable outcomes under different situations. Due to the fact that Malaysian literature on leadership styles and organizational performance is not being enriched, there is an urge for the researcher to perform a robust and rigorous research by examining the relationship of leadership styles and organizational performance among academics leaders in education service environment. This study examines the leadership styles of the academic leaders in the Malaysian Public Universities in Klang Valley area. It is found that transformational leadership was highly practiced by most academic leaders in Malaysian Public Universities in Klang Valley area. Transformational leadership supported knowledge sharing among educators. Further research is needed to understand the characteristics, skills, and preparation needed for aspiring an individual seeking to move into the position of faculty leaders.